2018
DOI: 10.1007/s10714-018-2354-8
|View full text |Cite
|
Sign up to set email alerts
|

General relativistic effects in the structure of massive white dwarfs

Abstract: In this work we investigate the structure of white dwarfs using the Tolman-Oppenheimer-Volkoff equations and compare our results with those obtained from Newtonian equations of gravitation in order to put in evidence the importance of General Relativity (GR) for the structure of such stars. We consider in this work for the matter inside white dwarfs two equations of state, frequently found in the literature, namely, the Chandrasekhar and Salpeter equations of state. We find that using Newtonian equilibrium equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Albeit these objects exceed significantly the Chandrasekhar mass limit, they suffer from severe stability issues as discussed in the literature [15][16][17][18][19]. In [9][10][11][12][13] are found that white dwarfs with rotation and different topology for the magnetic field could reach masses up to 5M .…”
Section: Introductionmentioning
confidence: 99%
“…Albeit these objects exceed significantly the Chandrasekhar mass limit, they suffer from severe stability issues as discussed in the literature [15][16][17][18][19]. In [9][10][11][12][13] are found that white dwarfs with rotation and different topology for the magnetic field could reach masses up to 5M .…”
Section: Introductionmentioning
confidence: 99%
“…The rapid RN M31N 2008-12a also showed an early turn-on of the SSS phase, six days after the nova eruption (Henze et al 2015). The small 3270km radius of the WD photosphere as derived from the blackbody model of the peak SSS XRT spectrum in Section 3.11 is also indicative of a massive WD with M>1.25 M (Carvalho et al 2018).…”
Section: The Mass Of the Wdmentioning
confidence: 81%
“…Using the fitted blackbody temperature (∼ 100 eV) and the fixed luminosity (1.1×10 37 erg s −1 ), we derive a BB radius of ≈3270 km for the hot photosphere of the WD during the peak SSS emission. There are some caveats: (1) the assumption of a BB spectrum may not be valid and the temperature may not have the usual physical meaning; (2) the system is eclipsing, so the rim of the accretion disk may hide part of the WD emission; and (3) the theoretical radius of a 1.3 M WD is smaller than 2800 km (Carvalho et al 2018), which suggests the error in the blackbody temperature estimate is of order 8%. Figure 9 shows a comparison of four spectra obtained throughout the rise to peak count rate.…”
Section: Swift Xrt Spectramentioning
confidence: 99%
“…4, one can notice that the mass density of the general relativistic white dwarf is larger than the Newtonian one in the central region, where the major part of the white dwarf mass is concentrated. The central density of the white dwarf with a fixed mass 1.415 ⨀ is 1.61 10 g/cm in general relativity, 4.08 10 g/cm in Newtonian Gravity [19]. Effects of finite temperatures.In Fig.…”
mentioning
confidence: 99%
“…We have also reproduced independently the results obtained in the work of Carvalho et al, where they have shown the importance of general relativistic effects for white dwarfs. Following the work [19], in Fig. 3, we show the mass profile of the white dwarf for a fixed total mass 1.415 M ⨀ , where the importance of general relativistic effects is conspicuous.…”
mentioning
confidence: 99%